Proyectos integrados. Estado actual e implicaciones para el diagnóstico - Cardona Arango, A. (International Center for Tropical Agriculture, 1989)
The role of integrated development projects in the planning of institutional activities in the agricultural sector is analyzed. CIAT's participation in the national integrated rural development program, DRI, with the cassava natural drying project for animal feed on Colombia's Atlantic Coast, is reviewed. The main characteristics of this project are listed. To help solve some of the problems identified (year-round production of dried cassava, expansion to other areas, high transportation costs), 2 new pilot projects are planned, namely (1) the production of CF from dried chips and (2) the production of balanced feed rations with dried cassava as the main source of carbohydrates. Two other projects currently underway have resulted in the production of high-quality CF for human consumption (bread, macaroni, porridges) by associations of small-scale cassava producers/processors and in the conservation and commercialization of fresh cassava in bags. These projects have diversified the market for the cassava producer, assuring greater possibilities of commercializing the product with positive economic returns (increased income). The Colombian government, in turn, has therefore recognized the importance of the crop, considering its potential for decreased wheat and sorghum imports. (CIAT)